1942
DOI: 10.1172/jci101295
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Foreign Surfaces on Blood Coagulation 12

Abstract: In the United States, the two-stage theory of blood coagulation is widely accepted. This theory recently reviewed by Quick (1) and Eagle (2) suggests that in the first stage prothrombin, calcium ion and thromboplastin interact to form thrombin. Thrombin, in the second stage, converts fibrinogen to fibrin. Plasma thromboplastin has been considered to be of platelet origin. The phenomenon of the initiation of coagulation when blood is shed has been considered by many investigators to be due to the disintegration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1944
1944
2003
2003

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 6 publications
(8 reference statements)
0
15
0
Order By: Relevance
“…The current experiments again demonstrate that celland "platelet-free" plasma does clot, and furthermore, demonstrate that the rate of prothrombin utilization during clotting of such plasma is a function of the degree of exposure to glass surface. The earlier work has been criticized because the test plasma was not shown to be platelet-free since platelet counts were not performed (1, 3, 5-7), or the methods of counting platelets made it impossible to evaluate the actual platelet levels (8). In more recent work (14), and in the current experiments, direct observation of undiluted plasma samples using the phase contrast microscope have eliminated these objections.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The current experiments again demonstrate that celland "platelet-free" plasma does clot, and furthermore, demonstrate that the rate of prothrombin utilization during clotting of such plasma is a function of the degree of exposure to glass surface. The earlier work has been criticized because the test plasma was not shown to be platelet-free since platelet counts were not performed (1, 3, 5-7), or the methods of counting platelets made it impossible to evaluate the actual platelet levels (8). In more recent work (14), and in the current experiments, direct observation of undiluted plasma samples using the phase contrast microscope have eliminated these objections.…”
Section: Resultsmentioning
confidence: 87%
“…." Since the original observations of Lister, many subsequent investigators have studied this phenomenon (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…of the plasma to be tested had been added. Coagulation times were performed by a modified (8) Lee and White method (9).…”
Section: Hematological Studiesmentioning
confidence: 99%
“…Pohle and Taylor (1937) first demonstrated that intramuscular use of this globulin substance was effective in correcting the clotting time in patients with haemophilia, but also demonstrated the refractory state induced by subsequent injections. The Thorndike also participated in the beginnings of the modern understanding of disseminated intravascular coagulation when Lozner and Taylor (1942) reported the effects of artificial surfaces on the initiation of coagulation and Tagnon et al (1942) studied the fibrinolytic activity of plasma. Lymphoma Henry Jackson Jr was the major contributor to morphological research in haematology at the Thorndike.…”
Section: Coagulationmentioning
confidence: 99%